Analisis Komparasi Brand Trust Dan Brand Awareness Terhadap Loyalitas Konsumen Pada Produk Kosmetik MS GLOW Dan Naavagreen Di Surabaya - Savitri, Septiani; Pratiwi, Ni Made; Pujianto, Agung (Universitas 17 Agustus 1945 Surabaya, 2021)
ABSTRACT The use of cosmetics has become an inseparable part of human life. Cosmetics are used as care products to maintain health and beautify themselves, the development of cosmetic products is also very fast. This is evidenced by the emergence of various types of cosmetic products with various brands. This study uses quantitative methods with survey research using a questionnaire as an instrument. The population in this study were all women and men who used MS GLOW and Naavagreen in Surabaya. The research sample used a non-probability sampling method with purposive sampling from 96 respondents. The data analysis technique used to answer the hypothesis is the independent sample t test. The results of this study indicate that all independent variables, namely Brand Trust and Brand Awareness, have differences in the dependent variable of Consumer Loyalty. The significant value of the Brand Trust variable is 0.000, followed by the Brand Awareness variable which has a value of 0.000 and the last variable dependent Consumer Loyalty has a significance value of 0.000. All variables have a significance value <0.05. which means that all independent variables Brand Trust and Brand Awareness have differences in Consumer Loyalty of MS GLOW and Naavagreen cosmetic products.Keywords: Brand Trust, Brand Awareness, Consumer Loyalty.